2021
DOI: 10.1029/2021jb022005
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Margin‐Wide Rupture Behaviors Along the Cascadia Megathrust With 3‐D Dynamic Rupture Simulations

Abstract: The Cascadia subduction zone megathrust dominates earthquake hazard in the United States Pacific Northwest. It is oft-cited that the probability of a magnitude ∼9 (M9) event occurring in the coming decades is between 10%-14% (Petersen et al., 2014). The most recent megathrust rupture in Cascadia occurred in 1700 A.D. and generated a transoceanic tsunami (Heaton & Hartzell, 1987). Matching amplitudes of historical tsunami records from Japan requires a magnitude between M8.7-9.2 for this earthquake (Satake et al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 114 publications
(214 reference statements)
5
35
0
Order By: Relevance
“…Additionally, a noteworthy feature of both models is that a supershear transition occurs within the gap region (Figures 2c and 2d). This transition is a direct result of our parameterization of the shear stress and strength of the megathrust between the seismogenic zone and the region hosting ETS (Andrews, 2010) and is consistent with the results of Ramos and Huang (2019) and Ramos et al (2021).…”
Section: Resultssupporting
confidence: 88%
“…Additionally, a noteworthy feature of both models is that a supershear transition occurs within the gap region (Figures 2c and 2d). This transition is a direct result of our parameterization of the shear stress and strength of the megathrust between the seismogenic zone and the region hosting ETS (Andrews, 2010) and is consistent with the results of Ramos and Huang (2019) and Ramos et al (2021).…”
Section: Resultssupporting
confidence: 88%
“…(Priest et al, 2010) produces similar tsunami amplitudes to those from our model shown in (b), both in the Pacific (c and d) and along the coastline (e). Also, a dynamic M w = 9.2 rupture (Ramos et al, 2021) derived from the Gaussian locking model (f) and our choice of locking model (g) result in similar tsunami amplitudes both in the Pacific (h and i) and along the coastline (j). The dots next to coastline show locations of virtual gauges.…”
Section: Discussionmentioning
confidence: 82%
“…Similarly, simulations based on state-of-the-art techniques are used as added sources of information (Frankel et al, 2018;Ramos et al, 2021;Ramos & Huang, 2019;Wirth et al, 2018).…”
Section: Figurementioning
confidence: 99%